2021
DOI: 10.1016/j.jval.2021.04.1284
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Value of Hope

Abstract: Background: 'Hope' is a construct in patient-centered value frameworks, but few studies have attempted to measure the value of hope separately from treatment-related gains in quality of life and survival to support its application in economic evaluation.Objective: To generate quantitative information on the "value of hope".Methods: We designed a discrete-choice experiment in which treatment alternatives varied the probability of achieving 10year survival, expected survival as the weighted sum of short-term and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 24 publications
0
16
1
Order By: Relevance
“…It has been argued that the QALY insufficiently captures the value of gene therapies and that additional value elements, such as the value of a cure (ie, nonhealth-related welfare benefits, such as being able to do more future-planning), should also be considered. Although there may indeed be benefits beyond QALYs to being completely cured of a condition, our findings suggest that, on average, the monetary value of these additional benefits would have to be Int$21 287417 per patient for the DNMB to no longer be negative, which arguably is implausibly high, especially in the light of a recent study by Reed et al 32 in which much lower figures are found for the "value of hope". The genetic therapies included in our analysis were treatments for spinal muscle atrophy (Spinraza, Zolgensma) and loss of vision because of inherited retinal dystrophy (Luxturna), and CAR-T cell therapies.…”
Section: Interpretation Resultscontrasting
confidence: 58%
“…It has been argued that the QALY insufficiently captures the value of gene therapies and that additional value elements, such as the value of a cure (ie, nonhealth-related welfare benefits, such as being able to do more future-planning), should also be considered. Although there may indeed be benefits beyond QALYs to being completely cured of a condition, our findings suggest that, on average, the monetary value of these additional benefits would have to be Int$21 287417 per patient for the DNMB to no longer be negative, which arguably is implausibly high, especially in the light of a recent study by Reed et al 32 in which much lower figures are found for the "value of hope". The genetic therapies included in our analysis were treatments for spinal muscle atrophy (Spinraza, Zolgensma) and loss of vision because of inherited retinal dystrophy (Luxturna), and CAR-T cell therapies.…”
Section: Interpretation Resultscontrasting
confidence: 58%
“…Using a discrete choice experiment, Hauber et al 20 found that patients diagnosed of nonsmall cell lung cancer expressed a preference for increasing best case survival (of the 85th percentile) relative to expected survival (of the 50th percentile). Nevertheless, a clearer presentation of the survival options presented in a similar discrete choice experiment by Reed et al 21 with respondents with a history of cancer found that although respondents preferred options with a 5% and 10% chance of long-term survival when holding constant expected survival, at a 20% chance of survival, preferences were reversed.…”
Section: Evidence For Including the Value Of Hope Based On Risk-seeki...mentioning
confidence: 97%
“…Another method to quantify ‘hope’ was presented by using a discrete choice experiment (DCE) ( 42 ). Using a DCE for 200 patients with cancer or a history of cancer, Reed et al.…”
Section: Consideration Of Risk Preferences In Standard Value Assessmentmentioning
confidence: 99%
“…First a pilot DCE was designed, and “participants were asked to assume that they had recently been diagnosed with cancer that had begun to metastasize” ( 42 ). Participants then had to consider choices “when expected survival was three years, with a given chance of 10-year survival, or a case with certain 3-year survival outcome (i.e., 10-year survival was zero)” ( 42 ). After piloting the DCE using general participants, cancer patients were asked to complete the online DCE survey.…”
Section: Consideration Of Risk Preferences In Standard Value Assessmentmentioning
confidence: 99%
See 1 more Smart Citation